Satisfaction of users of Psychosocial Care Centers - Soares, Fabiana Cruz (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2019)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: evaluate the satisfaction of users with the care provided at the Psychosocial Care Centers and its association with clinical and sociodemographic factors. METHOD: this cross-sectional study was conducted with 55 users from 5 Psychosocial Care Centers. The sociodemographic and clinical characteristics were obtained through an individual structured interview. The abbreviated version of the Mental Health Services Satisfaction Scale (SATIS-BR) was used for data collection. RESULTS: were descriptively analyzed and simple and multiple logistic regression models were adjusted for analysis of associations, estimating the gross and adjusted odds ratio, with the respective confidence intervals of 95%. Results: the age average of the sample was 40.1 (±12.4) years and the degree of satisfaction average was 4.56 (±0.45). Users with less education (primary school) had 5 times more chance of having less satisfaction (p<0.05). Users with frequency of intensive monitoring were 5 times more likely to have less satisfaction than users who receive monthly monitoring (p<0.05). CONCLUSION: the majority of users are satisfied with the service and factors such as low education and higher frequency of monitoring influenced the satisfaction.